2009
DOI: 10.1016/j.yebeh.2008.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Subjective perception of cognition is related to mood and not performance

Abstract: Background-Clinicians monitor cognitive effects of drugs primarily by asking patients to describe their side effects. We examined the relationship of subjective perception of cognition to mood and objective cognitive performance in healthy volunteers and neurological patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
64
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(77 citation statements)
references
References 39 publications
11
64
1
1
Order By: Relevance
“…These findings may be explained by the fact that patients with depressive symptoms are likely to overestimate their cognitive symptoms 30 . This is consistent with Marino et al 12 who concluded that PD patients with memory-related complaints showed mood disorders and that there was no relationship between subjective complaints and objective cognitive impairment.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…These findings may be explained by the fact that patients with depressive symptoms are likely to overestimate their cognitive symptoms 30 . This is consistent with Marino et al 12 who concluded that PD patients with memory-related complaints showed mood disorders and that there was no relationship between subjective complaints and objective cognitive impairment.…”
supporting
confidence: 92%
“…In line with this, it has recently been shown that subjective cognitive complaints (SCC) may harbor early dementia 10,11 . On the other hand, it has been also found that cognitive complaints in the absence of dementia might be attributed to an underlying mood disorder 12 .…”
mentioning
confidence: 99%
“…It may be that mood disorders cause symptoms of cognitive dysfunction or that cognitive dysfunction (not captured by objective testing) can cause symptoms of anxiety and depression. The relationship between mood and cognitive symptoms may also be mediated by other factors, such as the well-documented interdependent relationships with antiepileptic drug therapy and seizure frequency (Elixhauser et al 1999;Meador 2002;Marino et al 2009). This may well have been relevant in our refractory population recruited in a specialist epilepsy clinic, with 60% prescribed polytherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Some degree of cognitive decrease is present even in patients with newly diagnosed epilepsy, prior to the beginning of antiepileptic therapy [52]. Moreover, subjective perception of cognitive effects is related more to mood than objective performance [30]. The low score on cognitive functioning could be the result of comorbid mood disorders, since the majority (65.4%) of patients had abnormal BDI scores.…”
Section: Discussionmentioning
confidence: 99%